EXPRESSIVE SPEECH IN TWITTER ACCOUNT (X) @UM_FESS - Melani, Fentik; Suyitno, Imam (Jurusan Sastra Indonesia, 2024)
This study examines expressive speech on the Twitter account @um_fess, an anonymous State University of Malang student community menfess account. This study aims to describe the form of expressive speech, speech strategies, and the meaning of speech on the account with a descriptive qualitative approach, using student tweet data during April 2023. Data analysis includes data reduction, data presentation, and conclusion drawing. The results show that expressive speech consists of declarative, interrogative, and imperative speech, which express feelings and experiences openly. The utterances are divided into short limited, and deep broad. Complete utterances provide full context, while incomplete utterances rely on contextual understanding. Speech strategies include direct and indirect approaches, with positive and negative politeness, and vague strategies. Literal meanings are able to convey intent clearly, while non-literal meanings are used to convey more complex feelings and criticisms.